writing for the self and escaping the pandemic ,A reading of unclaimed metters by rawiya yahyawi (مجلة إحالات, 2026)
In unclaimed letters carried by the postman, literary self turns to the art of writing as a form of catharsis for its inner complexities. Our study, titled « writing for the self and Escaping the pandemic, A Reading of Unclaimed metters by Rawiya Yahyawi » sheds light on the impact of COVID-19 on theauthor’s psyche and her endeavor to conront this pandemic through her literary writing, narrating stories from her past with family . we have concluded that the nature and essence of these letters differ from other literary genres as they convey the chemistry of the emotional impulse driving the act of writing.